An Insect- and Rain-Proof Net Raises the Production and Quality of Chinese Bayberry by Preventing Damage From Insects and Altering Bacterial Communities - Yu, Haiyue; Tian, Shengke; Huang, Qianbin; Chen, Jiuzhou; Wu, Yuping; Wang, Runze; Lu, Lingli (Frontiers in Plant Science, 2021)
Chinese bayberry (Myrica rubra) is a popular, nutrient- and antioxidant-rich fruit in Asia. However, it is susceptible to Drosophila during ripening, which disrupts production and causes economic loss. This study compared the effects insecticides, insect-proof nets (IPNs), and insect- and rain-proof nets (IRPNs) on Chinese bayberry production and quality. Drosophila were absent in fruits from IPN- or IRPN-treated trees but only significantly reduced by insecticides. IPNs and IRPNs significantly increased fruit diameter, weight, edible rate, and the Brix/acid ratio, and IRPNs had the strongest effect. Analysis of 16S rDNA showed that fruits collected from differently treated trees had unique bacterial communities. In IRPN fruits, Acetobacter and Gluconobacter were significantly decreased, reducing sugar consumption and disease; in addition, PICRUSt analysis predicted imputed functional profiles related to carbohydrate and nitrogen metabolism and mineral transport for fruit growth and development. This study proposed the use of IRPNs for improving Chinese bayberry production and quality.